2016
DOI: 10.1021/acs.nanolett.5b04014
|View full text |Cite
|
Sign up to set email alerts
|

Phonon Scattering Dynamics of Thermophoretic Motion in Carbon Nanotube Oscillators

Abstract: Using phonon wave packet molecular dynamics simulations, we find that anomalous longitudinal acoustic (LA) mode phonon scattering in low to moderate energy ranges is responsible for initiating thermophoretic motion in carbon nanotube oscillators. The repeated scattering of a single mode LA phonon wave packet near the ends of the inner nanotube provides a net unbalanced force that, if large enough, initiates thermophoresis. By applying a coherent phonon pulse on the outer tube, which generalizes the single mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 42 publications
1
16
0
3
Order By: Relevance
“…In the unconstrained MD simulations of thermophoresis 29,[33][34][35][36][37]40,41 al. 29 and then, in a similar context, reported by Zambrano et al 36 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the unconstrained MD simulations of thermophoresis 29,[33][34][35][36][37]40,41 al. 29 and then, in a similar context, reported by Zambrano et al 36 .…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the practical use of thermophoresis in future CNT-based nanofluidic devices requires the feasibility of achieving predictable and controllable thermophoretic water transport inside CNTs. To date, despite the important efforts that have been devoted to investigate thermophoresis inside and outside CNTs [29][30][31][32][33][34][35][36][37][38][39][40][41] , the interplay between applied thermal gradient, thermophoretic velocity, solid-liquid friction [42][43][44][45] and thermophoretic force 30,33,36 in a water/CNT system, has not been studied. In this letter, we present an atomistic study of the kinetics associated with thermophoresis of water nanodroplets confined inside single wall carbon nanotubes and its interplay with the solid-liquid friction force.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, it was shown via phonon wave packet molecular dynamics (MD) simulations in CNTs that thermophoretic motion is driven by the scattering of LA phonons between the external and internal CNTs (12). In all of theoretical studies so far, the temperature gradient ∆T was nonetheless considered as the relevant quantity which controls thermophoresis as in Eq.…”
Section: Significancementioning
confidence: 99%
“…The temperature difference gives rise to a net imbalance of phonon population between the two sides, n hot and n cold . In coaxial nanotubes, Prasad et al (12) showed how a phonon wave packet traveling in the outer (longer) tube scatters at the edges of the inner (shorter) tube, exchanging energy and momentum. This "push" from a single wave is felt identically whether it comes from the hot reservoir or from the cold reservoir.…”
Section: Cluster Thermophoretic Motion and Forcementioning
confidence: 99%
See 1 more Smart Citation